1997
DOI: 10.1126/science.277.5323.219
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Behavior of Sound Velocity and Attenuation in Liquid Fe-Ni-S

Abstract: The compressional wave velocity in molten iron containing 5 percent nickel and 10 percent sulfur increased with increasing temperature. This anomalous behavior was determined to be attributable to the presence of sulfur, which conditions the formation of large molecular units in the liquid. Temperature-induced breakup of macromolecular units resulted in greater packing efficiency and an increased velocity. Ten percent sulfur increased attenuation by one to two orders of magnitude compared with liquid iron. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 25 publications
6
24
2
Order By: Relevance
“…It should be pointed out that, although the abovementioned results of TI-LLST are limited in the investigations of ourselves, the similar phenomena have been observed by other groups with different resorts like viscosity [49,50], density and sound velocity methods [51,52], as well as computer simulations [53,54]. For example, by high-resolution measurements of the density, the heat capacity and the static structure factor, scientists out of Israel, USA and France found that a temperature-driven liquid-liquid structural transformation takes place quite above liquidus of Bi [55].…”
Section: Kinetics and Thermodynamics Of Temperature-induced Liquid-lisupporting
confidence: 76%
“…It should be pointed out that, although the abovementioned results of TI-LLST are limited in the investigations of ourselves, the similar phenomena have been observed by other groups with different resorts like viscosity [49,50], density and sound velocity methods [51,52], as well as computer simulations [53,54]. For example, by high-resolution measurements of the density, the heat capacity and the static structure factor, scientists out of Israel, USA and France found that a temperature-driven liquid-liquid structural transformation takes place quite above liquidus of Bi [55].…”
Section: Kinetics and Thermodynamics Of Temperature-induced Liquid-lisupporting
confidence: 76%
“…On the other hand, the quantity actually reported in Ref. [5], which is inversely proportional to the attenuation per wavelength, decreases with increasing T at a rate which can be estimated as 0.033 K −1 . Hydrodynamically, the main contributions to acoustic attenuation are the longitudinal viscosity and a heat-conduction term.…”
Section: Introductionmentioning
confidence: 97%
“…Our interest on these molten alloys was awaken from a paper by Nasch et al [5] that has reported a highly anomalous behavior of the ultrasonic sound velocity c v (T ) and attenuation a(T ) in the mixture 85%Fe5%Ni10%S for temperatures above melting (T m =1650 K) up to 2000 K under its saturated vapor pressure. In fact and contrary to data for the pure liquid-metal components [6], the sound velocity for such a sample increases with temperature with a rate of dc/dT = 0.625 m s −1 K −1 at 2000 K. This figure is to be compared with the decrease of the sound velocity with temperature for pure elements [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, extensive researches in recent decades may provide some indirect evidence to suggest that it is the different liquid states that give rise to diverse solidification behaviors and properties. By means of internal friction [22], liquid X-ray diffraction [23], neutron diffraction and small-angle neutron scattering [24], viscosity [25], density and sound velocity [26], as well as computer simulations [27] etc., lots of research groups found and convinced a new physical phenomenon: temperature induced liquid liquid structural transition (TI-LLST) occurred in some single or multiple component melts well above their liquidus. More significantly, it was found the solidification structures and some relevant properties indeed changed when solidified out of the melts after experiencing TI-LLST [28].…”
Section: Introductionmentioning
confidence: 99%